ANALISIS CAMPUR KODE PADA LAGU LOS DOL KARYA DENNY CAKNAN - Syahrul Aditya Wijayanto; Hidayat Nur Septiadi; Helmi Septiani (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
The song "Los Dol" by Denny Caknan has become a phenomenon among listeners, especially the younger generation, thanks to its catchy melody and memorable lyrics. The main attraction of this song lies in the use of code mixing, where Denny Caknan combines Javanese and Indonesian. Javanese provides a strong local feel, while Indonesian makes the song more accessible to listeners who are not fluent in Javanese. The lyrics of "Los Dol" not only convey feelings, but also reflect social and cultural realities. Denny Caknan inserts deep Javanese terms, and the Indonesian context helps listeners understand the meaning he wants to convey. This song serves as a means of preserving Javanese language and culture and creating a space for dialogue between generations. Overall, "Los Dol" is a work of art rich in meaning and cultural value, showing how music can strengthen cultural identity and facilitate communication between generations.